Self Care Management-Holistic Psychospiritual Care on Independence, Glucose Level, and Hba1c of Type 2 Diabetes Mellitus Patient - Kusnanto Kusnanto (Universitas Airlangga, 2012)
Introduction: Diabetes mellitus is a kind of incurable chronic disease that actually manageable. The global prevalence tends to increase due to less self management of the disease and the impact of it was health condition declines physically, psychologically, socially, and spiritually. There were so many interventions implemented but failed to give positive improvement in patient's holistic condition which is lead to complications. The purpose of this research was to improve patient independency in managing the disease and to explain changes in blood glucose and HbA1C levels through self care management-holistic psychospiritual care model.Method: Patient newly diagnose with type 2 diabetes mellitus at Public Health Centre Kebonsari was selected with purposive sampling and divided into two groups. Each group contains 25 patients. Intervention group was given self care management model development with self diabetes management module. The intervention was given ﬁve times in three months. Before and after intervention patient was observed for blood glucose level of 2 hours before and after meal, and also HbA1C level. Questionnaire was given to patient. The data then analyzed using wilcoxon, mann whitney, and student-t test.Result: The result of this research showed patient with type 2 diabetes have independency improvement and lower blood glucose level of 2 hours before and after meal and also decreased HbA1C after intervention.Discussion: Self Care Management-Holistic Psychospiritual Care Model improves patient independency in managing their disease, lowering blood glucose and HbA1C levels.